2014
DOI: 10.3109/17435390.2014.933903
|View full text |Cite
|
Sign up to set email alerts
|

Thirteen-week study of toxicity of fiber-like multi-walled carbon nanotubes with whole-body inhalation exposure in rats

Abstract: Cancer development due to fiber-like straight type of multi-walled carbon nanotubes (MWCNTs) has raised concerns for human safety because of its shape similar to asbestos. To set concentrations of MWCNT for a rat carcinogenicity study, we conducted a 13-week whole body inhalation study. F344 male and female rats, 6-week-old at the commencement of the study, were exposed by whole-body inhalation to MWCNT at concentrations of 0, 0.2, 1 and 5 mg/m(3) with a generation and exposure system utilizing the cyclone sie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 32 publications
4
90
1
Order By: Relevance
“…However, globally, each step has been demonstrated to occur among the various types of CNTs. For MWCNTs, each step is completed, by one or another MWCNTs subtype, and as documented by several independent studies (Muller et al 2008a; Ryman-Rasmussen et al 2009; Aiso et al 2010; Porter et al 2010, 2013; Mercer et al 2011; Treumann et al 2013; Sargent et al 2014; Kasai et al 2015). New reported studies extend these results to additional types of CNTs, including an IP study showing carcinogenicity of four samples of MWCNTs (Rittinghausen et al 2014), and a recent article that reports malignant and nonmalignant lung tumors and mesothelioma in rats exposed by trans-tracheal intrapulmonary spraying to three different fractions of MWCNT-N (Suzui et al 2016).…”
Section: Discussion Of Review Findingsmentioning
confidence: 99%
“…However, globally, each step has been demonstrated to occur among the various types of CNTs. For MWCNTs, each step is completed, by one or another MWCNTs subtype, and as documented by several independent studies (Muller et al 2008a; Ryman-Rasmussen et al 2009; Aiso et al 2010; Porter et al 2010, 2013; Mercer et al 2011; Treumann et al 2013; Sargent et al 2014; Kasai et al 2015). New reported studies extend these results to additional types of CNTs, including an IP study showing carcinogenicity of four samples of MWCNTs (Rittinghausen et al 2014), and a recent article that reports malignant and nonmalignant lung tumors and mesothelioma in rats exposed by trans-tracheal intrapulmonary spraying to three different fractions of MWCNT-N (Suzui et al 2016).…”
Section: Discussion Of Review Findingsmentioning
confidence: 99%
“…instillation or exposure via airways (Mercer et al, 2010;Murphy et al, 2013;Porter et al, 2013;Kasai et al, 2015Kasai et al, , 2016Suzui et al, 2016;Fukushima et al, 2018). Likewise, several studies in vitro have shown that IL-1 signaling may also be important in cellular responses to nanomaterials in general, but the role of IL-1 in cellular responses of MWCNTs in the pleura has not been studied in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A recent 13-week whole body inhalation study on rats using different concentrations of MWCNTs demonstrated granulomatous changes (at 0.2 mg/m 3 in males, 1 and 5 mg/m 3 in females), focal fibrosis of the alveolar wall (at 1 mg/m 3 or higher for both sexes) and increased inflammatory parameters (concentration dependently in both sexes from 0.2 mg/m 3 ). Inflammatory infiltration in the visceral pleural and subpleural areas was induced only at 5 mg/m 3 , and it was concluded that 0.2 mg/m 3 was the threshold for respiratory tract toxicity [97]. …”
Section: Toxicology and Environmental Concernsmentioning
confidence: 99%